Improving mathematical problem-solving skills in ratio through the application of problem-based learning - Maharani, Zulfa; Sakur; Armis (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
The main objectives of this study were to improve the quality of learning activities and enhance students' skills in Mathematical Problem Solving Skills. The research was conducted during the even semester of the 2023/2024 school year by implementing classroom action research over two cycles on ratio content. The subjects of this study were 41 students from class VII-3 of SMPN 42 Pekanbaru. The learning tools used in the study included the Flow of Learning Objectives, teaching modules, learner worksheets, teaching materials on ratio content, and assessment tools. The data collection instruments consisted of learner and teacher activity sheets and tests for assessing Mathematical Problem Solving Skills. Data analysis on the improvement of the learning process was obtained based on the activity sheets from both learners and teachers. Additionally, the improvement of students' Mathematical Problem Solving Skills was assessed through tests conducted at the end of each cycle. The results of the observation sheets from cycles I and II showed that the learning process improved with each meeting. The students' scores in Mathematical Problem Solving Skills increased from the initial test to the cycle I test by 11.73 points, with an initial average of 43.69 and a cycle I test average of 55.42. From the cycle I test to the cycle II test, there was an increase of 18.25 points, with an average score of 73.67 in the cycle II test. Therefore, the results of this research, conducted using the Problem-Based Learning model, indicate a potential to improve the learning process and enhance students' problem-solving skills.